Solving the maximum flow problem with the lift-to-front algorithm - Hotler Manurung; Tinus Ginting; Adnan Surbakti; Julida Harahap; Resep Sembiring (Institute of Computer Science (IOCS), 2023)
Maximum flow network is an optimization problem related to the effort to optimize the system in maximizing the scale of materials that can be shipped from source to destination based on the system's capabilities. This problem can be solved using the lift-to-front algorithm. The lift-to-front algorithm is based on the application of lists by maintaining a list of vertices in the network. When a vertex is selected it is moved to the front of the list (hence the method is called 'lift-to-front') and the method starts its review once again. The results show that the designed software can demonstrate the application of the Lift-to-Front Algorithm in solving the Maximum Flow problem.